Exploring Flexible Learning Experiences - Espineda-Villanueva, Jovita (Future Science / FSH-PH Publications, 2024)
Flexible learning is a popular mode of learning in this 21st century since it allows flexibility in almost all aspects of the teaching and learning process. The study explored the flexible learning experi-ences of college students enrolled in the school year 2022-2023. The focus were in terms of internet connection, communication, conferencing platform, online teaching strategies, assessment of learning, student participation and submission of requirements. Results revealed that internet connection is a problem as they en-gaged in flexible learning modality since most of the activities re-lated to flexible learning uses internet. Indeed flexible learning is a struggle to many students. The study made use of mixed method as its research design. After considering several literature about flexible learning, a survey questionnaire was drafted and eventual-ly validated by experts prior to its distribution to the respondents via google form. The data gathered for the quantitative part were treated using weighted mean and a 5 point Likert Scale was used. A corresponding verbal interpretation of 5 Always, 4 Often, 3 Sometimes, 2 Seldom and -1 Never was also used. Weighted mean was used to treat gathered data. Likewise, an unstructured inter-view about the challenges encountered in flexible learning was also conducted through online via conferencing platforms Qualita-tive data gathered from interviews were treated using thematic analysis. Result of the study will serve as basis to an intervention program to address concerns on flexible learning.